Effect of moisture content and mix proportion of concrete on efficiency of laser scabbling. (June 2022) - Heo, Seong-Uk; Kim, Ji-Hyun; Oh, Seong Yong; Lim, Gwon; Nam, Sungmo; Kim, TaekSoo; Park, Hyunmin; Chung, Chul-Woo
Abstract: Laser scabbling is one of the options that can be used for removal of contaminated concrete when decommissioning and dismantling of nuclear power plant. Laser scabbling can be advantageous for such purpose because laser can transmit through long-distance and the system operates remotely in dry condition while minimizing the human access to the radioactively contaminated area. In order to investigate the applicability of laser scabbling on concrete, the experimental program was conducted on concrete with various moisture content, fine aggregate ratio with different paste content. According to the results, concrete in oven dry condition showed no efficiency on laser scabbling. The surface of the concrete was vitrified as a result. However, a 5 kW fiber laser with 900 mm stand-off distance was successfully applied for laser scabbling of air dry and saturated surface dry concretes. It was found that the moisture is a prerequisite requirement for successful laser scabbling of concrete. The changes in fine aggregate ratio and paste content did not affect the efficiency of laser scabbling.